The coordinated regulation mechanism of rice plant architecture and its tolerance to stress - Zhao, Huibo; Liu, Xiong; Wang, Jiajia; Qian, Qian; Zhang, Guangheng (Frontiers in Plant Science, 2022)
Rice plant architecture and stress tolerance have historically been primary concerns for rice breeders. The "Green Revolution" and super-rice breeding practices have demonstrated that ideal plant architecture can effectively improve both stress tolerance and yield. The synergistic selection and breeding of rice varieties with ideal architecture and stress tolerance can increase and stabilize yield. While rice plant architecture and stress tolerance are separately regulated by complicated genetic networks, the molecular mechanisms underlying their relationships and synergism have not yet been explored. In this paper, we review the regulatory mechanism between plant architecture, stress tolerance, and biological defense at the different level to provide a theoretical basis for the genetic network of the synergistic regulation and improvement of multiple traits.